Thromboelastometry and Platelet Function during Acclimatization to High Altitude - Rocke, Alistair S.; Paterson, Gordon G.; Barber, Matthew T.; Jackson, Alexander I. R.; Main, Shona; Stannett, Calum; Schnopp, Martin F.; Baillie, J. Kenneth; Horne, Elizabeth H.; Moores, Carl; Harrison, Paul; Nimmo, Alastair F.; Thompson, A. A. Roger (Thrombosis and Haemostasis, 2018)
Interaction between hypoxia and coagulation is important given the increased risk of thrombotic diseases in chronically hypoxic patients who reside at sea level and in residents at high altitude. Hypoxia alters the proteome of platelets favouring a prothrombotic phenotype, but studies of activation and consumption of specific coagulation factors in hypoxic humans have yielded conflicting results. We tested blood from 63 healthy lowland volunteers acclimatizing to high altitude (5,200 m) using thromboelastometry and assays of platelet function to examine the effects of hypoxia on haemostasis. Using data from two separate cohorts of patients following identical ascent profiles, we detected a significant delay in clot formation, but increased clot strength by day 7 at 5,200 m. The latter finding may be accounted for by the significant rise in platelet count and fibrinogen concentration that occurred during acclimatization. Platelet function assays revealed evidence of platelet hyper-reactivity, with shortened PFA-100 closure times and increased platelet aggregation in response to adenosine diphosphate. Post-expedition results were consistent with the normalization of coagulation following descent to sea level. These robust findings indicate that hypoxia increases platelet reactivity and, with the exception of the paradoxical delay in thromboelastometry clotting time, suggest a prothrombotic phenotype at altitude. Further work to elucidate the mechanism of platelet activation in hypoxia will be important and could impact upon the management of patients with acute or chronic hypoxic respiratory diseases who are at risk of thrombotic events.
Keywords: hypoxia; high altitude; haemostasis; platelet function; thromboelastometry